Engaging Bodies : The Politics and Poetics of Corporeality - Albright, Ann Cooper (Book collections on Project MUSE., 2013)
For the author, dancing is a physical inquiry, a way of experiencing and participating in the world, and her writing reflects an interdisciplinary approach to seeing and thinking about dance. In her engagement both as a dancer and a scholar, the author draws on her kinesthetic sensibilities as well as her intellectual knowledge to articulate how movement creates meaning. -- Publisher's description.